2022
DOI: 10.1177/11772719221107765
|View full text |Cite
|
Sign up to set email alerts
|

Glycerophosphoinositol is Elevated in Blood Samples From CLN3Δex7-8 pigs, Cln3Δex7-8 Mice, and CLN3-Affected Individuals

Abstract: Introduction: CLN3 Batten disease is a rare pediatric neurodegenerative lysosomal disorder caused by biallelic disease-associated variants in CLN3. Despite decades of intense research, specific biofluid biomarkers of disease status have not been reported, hindering clinical development of therapies. Thus, we sought to determine whether individuals with CLN3 Batten disease have elevated levels of specific metabolites in blood. Methods: We performed an exhaustive metabolomic screen using serum samples from a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 20 publications
4
16
0
Order By: Relevance
“…We could not detect a decrease of cln3 mRNA levels in MUT1, reducing the chance that transcriptional adaptation mechanisms (triggered by mutant mRNA decay) are compensating cln3 loss-of-function phenotypes in our zebrafish model (El-Brolosy et al 2019). Finally, the very distinct accumulation of GPDs and decrease of BMP species in MUT1 larvae confirm that we have indeed successfully knocked out Cln3 function, as the exact same metabolic changes were measured in samples derived from patients with CLN3 disease (Hobert and Dawson 2007; Brudvig et al 2022; Laqtom et al 2022). The association between BMPs and CLN3 has been known for many years, with metabolic labeling studies showing early on that CLN3 may be involved in BMP synthesis (Hobert and Dawson 2007).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…We could not detect a decrease of cln3 mRNA levels in MUT1, reducing the chance that transcriptional adaptation mechanisms (triggered by mutant mRNA decay) are compensating cln3 loss-of-function phenotypes in our zebrafish model (El-Brolosy et al 2019). Finally, the very distinct accumulation of GPDs and decrease of BMP species in MUT1 larvae confirm that we have indeed successfully knocked out Cln3 function, as the exact same metabolic changes were measured in samples derived from patients with CLN3 disease (Hobert and Dawson 2007; Brudvig et al 2022; Laqtom et al 2022). The association between BMPs and CLN3 has been known for many years, with metabolic labeling studies showing early on that CLN3 may be involved in BMP synthesis (Hobert and Dawson 2007).…”
Section: Discussionsupporting
confidence: 72%
“…5B) , whereas glycerophosphoethanolamine (GPE) was not significantly changed and glycerophosphoserine (GPS) was not detected in the extracts. While this work was ongoing, accumulation of GPDs has also been found in yeast and mammalian models of CLN3 deficiency (Laqtom et al 2022; Brudvig et al 2022), suggesting that CLN3 plays a highly conserved role in maintaining normal GPD levels across species. Phospholipid precursors such as phosphocholine and phosphoethanolamine were also detected at significantly higher levels in the mutant compared to WT larvae (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Structurally, CLN3 encodes a transmembrane lysosome protein whose C- and N-ends localise to the cytoplasm 106 . While CLN3 function remains not fully elucidated, recent studies have demonstrated that it is required for glycerophospholipid catabolism 107,108 . Glycerophospholipids are key structural components of cell membranes, but also play a variety of regulatory roles, including in innate immunity 109 .…”
Section: Discussionmentioning
confidence: 99%
“…CLN3 codes for a 468-amino acid predicted transmembrane protein that is implicated in many cellular pathways but awaiting a clearly defined function . Recent studies identified elevated levels of glycerophosphodiester species in CLN3 mouse and pig models and CLN3-affected individuals, , with the work from Laqtom et al suggesting an essential role of CLN3 protein in the clearance of these compounds from the lysosome. The most common disease-associated variant, a 966-base pair deletion present in ∼80% of chromosomes in affected individuals, is predicted to remove exons 7 and 8 and trigger either nonsense-mediated mRNA decay , or production of a truncated product with novel function. …”
Section: Introductionmentioning
confidence: 99%